Vitamin C and Turmeric Attenuate Bax and Bcl-2 Proteins' Expressions and DNA Damage in Lead Acetate-Induced Liver Injury - Ahlam M. Alhusaini; Laila M. Faddah; Iman H. Hasan; Somayah J. Jarallah; Shrouq H. Alghamdi; Norah M. Alhadab; Amira Badr; Najlaa Elorabi; Enas Zakaria; Abeer Al-anazi (SAGE Publishing, 2019)
Background: Lead is a common environmental and occupational pollutant which induced multiorgans dysfunction. The present study was designed to investigate the hepatoprotective effects of turmeric (TUR) and/or vitamin C (Vit-C) alone or together against lead acetate toxicity and to explore novel molecular pathways. Method: Acute hepatotoxicity was induced by lead acetate (100 mg/kg/day, i.p.) in male rats, and the effect of TUR (200 mg/kg/day, orally) and/or Vit-C (250 mg/kg/day, orally) along with lead acetate for 7 days was studied. Results: Lead acetate increased serum alanine transaminase, aspartate transaminase, lactate dehydrogenase, hepatic lipid peroxidation and nitric oxide; while, hepatic superoxide dismutase and glutathione activities were downregulated. Hepatic Bcl-2-associated X (Bax) and B-cell lymphoma-2 (Bcl-2) proteins expressions were altered and hepatic DNA damaged was increased as well. Liver/body weight ratio was decreased. Hematoxylin and eosin demonstrated that lead acetate induced focal areas of massive hepatic degeneration of the hepatocytes. Treatment with both antioxidants ameliorated all the altered parameters and induced marked improvement of liver architecture. Conclusion: The combination of TUR and Vit-C has shown the most protective effects against lead acetate-induced hepatotoxicity.